Remodeling of the periodontal ligament and alveolar bone during axial tooth movement in mice with type 1 diabetes - Li, Wenjin; Zheng, Jing; Xu, Yao; Niu, Weiran; Guo, Dong; Cui, Jianing; Bian, Wenjin; Wang, Xiaohui; Niu, Jinliang (Frontiers in Endocrinology, 2023)
Objectives To observe the elongation of the axial tooth movement in the unopposed rodent molar model with type 1 diabetes mellitus and explore the pathological changes of periodontal ligament and alveolar bone, and their correlation with tooth axial movement. Methods The 80 C57BL/6J mice were randomly divided into the streptozotocin(STZ)-injected group (n = 50) and the control group (n = 30). Mice in the streptozotocin(STZ)-injected group were injected intraperitoneal with streptozotocin (STZ), and mice in the control group were given intraperitoneal injection of equal doses of sodium citrate buffer. Thirty mice were randomly selected from the successful models as the T1DM group. The right maxillary molar teeth of mice were extracted under anesthesia, and allowed mandibular molars to super-erupt. Mice were sacrificed at 0, 3, 6,9, and 12 days. Tooth elongation and bone mineral density (BMD) were evaluatedwas evaluated by micro-CT analysis(0,and 12 days mice), and conventional HE staining, Masson staining and TRAP staining were used to observe the changes in periodontal tissue(0, 3, 6, 9, and 12 days mice). The expression differences of SPARC, FGF9, BMP4, NOGGIN, and type I collagen were analyzed by RT-qPCR. Results After 12 days of tooth extraction, our data showed significant super-eruption of mandibular mouse molars of the two groups. The amount of molar super-eruption in the T1DM group was 0.055mm(±0.014mm), and in the control group was 0.157(±0.017mm). The elongation of the T1DM mice was less than that of the control mice(P<0.001). It was observed that the osteoclasts and BMD increased gradually in both groups with the time increasing. Compared with the control group, the collagen arrangement was more disordered, the number of osteoclasts was more(P<0.05), and the increase of bone mineral density was lower(2.180±0.007g/cm3 vs. 2.204±0.006g/cm3, P<0.001) in the T1DM group. The relative expression of SPARC, FGF9, BMP4, and type I collagen in the two groups increased with the extension of tooth extraction time while NOGGIN decreased. The relative expression of all of SPARC, FGF9, BMP4, and type I collagen in the T1DM group were significantly lower, and the expression of NOGGIN was higher than that in the control group (P<0.05).